Filosofias da linguagem pós-estruturalistas e decolonialidades: contribuições para a formação docente? - Daniel Ferraz; Maria Cecília Soares de Paula Mendes (Revista Odisséia, 2021)
This article explores possible connections between the post-structuralist philosophies of language (in the precepts of Wittgenstein, 1999; Derrida, 2002 and Foucault, 1999) and decolonial studies (in the precepts of Quijano, 2005; Castro-Gómez & Grossfoguel, 2007 and Menezes de Souza, 2019, 2020). In the first section, we explore some perspectives on post-structuralist philosophies of language and the linguistic turn, such as changes in language views. In the second section, “From post-structuralism to decolonial?”, we briefly discuss three perspectives on decolonial studies, according to the aforementioned authors. Finally, in the section “For a paradigm shift in the English teacher education”, we seek to connect the philosophical dimension of the first two perspectives with teacher education, by suggesting that we need more discussion on teacher education of foreign language professionals from philosophical perspectives in our country.